2019
DOI: 10.1177/1557988319857009
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mental Health Service Utilization Among Men: A Systematic Review and Synthesis of Behavior Change Techniques Within Interventions Targeting Help-Seeking

Abstract: Compared to women, men are less likely to seek help for mental health difficulties. Despite considerable interest, a paucity in evidence-based solutions remains to solve this problem. The current review sought to synthesize the specific techniques within male-specific interventions that may contribute to an improvement in psychological help-seeking (attitudes, intentions, or behaviors). A systematic review identified 6,598 potential articles from three databases (MEDLINE, EMBASE, and PsycINFO). Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
143
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(174 citation statements)
references
References 106 publications
5
143
1
2
Order By: Relevance
“…Fathers may also feel added pressure to provide for their families in the face of economic hardship and rising unemployment rates, due, in part, to existing social norms and structures, while also taking on more childcare responsibilities than before the pandemic (Strauss, 2020). Studies show that men are less likely to seek out mental health services, and, therefore, it is crucial for social workers to employ a targeted approach for reaching out to fathers (Sagar-Ouriaghli et al, 2019). Conversely, parents between the ages of 18 and 34 had a lower likelihood of experiencing moderate or severe mental distress than those of aged 35 to 44.…”
Section: Discussionmentioning
confidence: 99%
“…Fathers may also feel added pressure to provide for their families in the face of economic hardship and rising unemployment rates, due, in part, to existing social norms and structures, while also taking on more childcare responsibilities than before the pandemic (Strauss, 2020). Studies show that men are less likely to seek out mental health services, and, therefore, it is crucial for social workers to employ a targeted approach for reaching out to fathers (Sagar-Ouriaghli et al, 2019). Conversely, parents between the ages of 18 and 34 had a lower likelihood of experiencing moderate or severe mental distress than those of aged 35 to 44.…”
Section: Discussionmentioning
confidence: 99%
“…In response to this, a systematic review investigating help-seeking interventions specifically in males was conducted [22]. This systematic review identified nine interventions targeting mental health help-seeking in men of different age groups, two of which were delivered to male students [23,24].…”
Section: Mrc Development: Identifying the Evidence Basementioning
confidence: 99%
“…As the systematic review conducted by Sagar-Ouriaghli et al [22] consisted of nine interventions with heterogenous clinical populations and dissimilar designs, a meta-analysis could not be conducted [34]. To provide a coherent summary, a novel method that identified the Behavioural Change Techniques (BCTs) was used [35].…”
Section: Mrc Development: Identifying the Evidence Basementioning
confidence: 99%
See 1 more Smart Citation
“…First, patients in this study were largely female and nearly exclusively white. This may reflect the gender and race differences in help-seeking patterns,40 41 healthcare utilisation41 42 and diagnosis rates,43 44 which has been well-documented in other studies. Further, the barriers to access experienced by Iowans of other racial and ethnic backgrounds may not be represented in these findings, indicating a need to research the experiences of racial and ethnic minorities obtaining rural mental healthcare, specifically.…”
Section: Discussionmentioning
confidence: 61%